Learner-oriented assessment (LOA) practice: the comparative study of self-assessment, peer assessment, and teacher assessment on EFL learners’ writing complicity, accuracy, and fluency (CAF), speaking CAF, and attitude - Anwar Hammad Al-Rashidi; Muhammad Asif; Masoumeh Ghasemi Vanani; Amhara Aberash (Language Testing in Asia, 2022)
Abstract As the effects of self-assessment, peer assessment, and teacher assessment on EFL learners’ writing CAF and speaking CAF have not examined in Iran, this research compared their effectiveness on developing Iranian EFL students’ writing CAF and speaking CAF. Moreover, this research examined the attitudes of EFL students towards the three types of assessments. To achieve these objectives, 75 Iranian intermediate EFL learners were selected based on a convenience sampling method and divided into three groups. Next, all groups were pretested on two skills of writing and speaking. Then, one group was taught writing and speaking skills by using teacher assessment, the second group was taught the same skills through using self-assessment; and the other group received the treatment by applying peer assessment. After an 18-session instruction, writing and speaking posttests were administered to the three groups, and also, three attitude questionnaires were distributed among them. The outcomes of one-way ANOVA tests revealed that the peer-assessment and self-assessment groups outflanked the teacher-assessment group on the writing and speaking posttests. The findings showed that the respondents of the three groups presented favorable attitudes towards the three sorts of assessments. It was concluded that the peer and self-assessment are useful techniques to develop EFL learners’ writing and speaking skills. At the end of the study, a couple of implications and recommendations were enumerated.